The vocal communication of the mongoose lemur (Eulemur mongoz): phonation mechanisms, acoustic features and quantitative analysis. Issue 3 (2nd July 2016) - Nadhurou, B.; Gamba, M.; Andriaholinirina, N.V.; Ouledi, A.; Giacoma, C.
Abstract : We recorded vocalisations of wild Eulemur mongoz groups in Madagascar and the Comoros Islands, as well as from habituated captive groups housed in European and Madagascan zoos. Each vocalisation was quantitatively described by means of an acoustic analysis procedure implemented in Praat, and vocal types were distinguished both by ear and by the visual screening of spectrograms. Vocal signals were then associated with the context in which they were produced, to explore whether they occur only in specific behavioural contexts or are uttered in a range of situations. We found that mongoose lemurs possess highly context-specific aerial alarm calls and territorial calls, while the 'croui-croui' is usually emitted to communicate between individuals regrouping at sunset. The other calls we recorded, such as those including low-pitched pulse trains sometimes followed by harmonic elements, were not tightly associated with a particular context. Mongoose lemur utterances included calls produced with closed mouths and the involvement of nasal resonance, or with constant degrees of mouth opening or mandible 'articulation' during phonation. We observed 15 vocal types, nine of which were entered into a multivariate model that classified vocal types with a high degree of reliability. The second and third formants played an important role in discriminating among types of calls.